Third- and Second-Harmonic Generation in All-Dielectric Nanostructures: A Mini Review - Liu, Tingting; Xiao, Shuyuan; Li, Baoli; Gu, Min; Luan, Haitao; Fang, Xinyuan (Frontiers in Nanotechnology, 2022)
Frequency conversion such as second- and third-harmonic generation is a fundamental physical process in nonlinear optics. The conventional nonlinear optical systems suffer from bulky size and cumbersome phase-matching conditions due to the inherently weak nonlinear response of natural materials. Aiming at the manipulation of nonlinear frequency conversion at the nanoscale with favorable conversion efficiencies, the recent research has shifted towards the integration of the nonlinear functionality into nanophotonics. Compared with plasmonic nanostructures showing high dissipative losses and thermal heating, all-dielectric nanostructures have demonstrated many excellent properties including low loss, high damage threshold, and controllable resonant electric and magnetic optical nonlinearity. In this review, we cover the recent advances in nonlinear nanophotonics, with special emphasis on third- and second-harmonic generation from all-dielectric nanoantennas and metasurfaces. We discuss the main theoretical concepts, the design principles and the functionalities of third- and second-harmonic generation processes from dielectric nanostructures, and provide an outlook on the future directions and developments of this research field.